Status oxidativo de cães com compressão medular toracolombar traumática - Oliveira, Ricardo Pimentel (2014)
With the increasing incidence of neurological injuries caused by spinal cord injuries, the aim of this study was to identify the oxidative status in dogs with spinal cord thoracolumbar trauma and establish if there is a pattern in common in the evaluated changes. To this end were quantified pro-oxidants agents, enzymatic antioxidants and non-enzymatic in injury dogs with thoracolumbar spinal cord acute. The research was developed in HV-UPF where a group was composed of eight dogs with spinal cord injury (IG), with a history of ataxia, decreased/proprioceptive loss, paresis of hind limbs and lumbar epaxial compression positive. For the confirmation of the compression, all dogs from the SCI were submitted to myelography from the deposition of non-ionic contrast in the subarachnoid space. The second group was composed of eight healthy dogs (CG), clinically healthy with blood count, renal biochemical profile and hepatic within the reference values for the species. The dogs of the two groups were submitted to blood sampling to quantify the oxidative status through the TBARS, CAT and GSH. It was also measured an acute-phase protein of positive character. The dogs injured showed higher values of TBARS when compared to the group of healthy patients. The values found by the CAT enzyme were similar for the two groups and the GSH identified lower results in the group of dogs with spinal cord trauma acute in relation to the healthy. The acute-phase protein showed similar values for the two groups. Thus, this research has identified the occurrence of oxidative stress, caused by an increase in lipid peroxidation and the activity of the defense system cellular antioxidant in the fight against the reactive oxygen species (ROS) in dogs with spinal cord compression thoracolumbar trauma